الأداء التدريسي لمعلمي اللغة العربية في السنة الأولى من المرحلة الثانوية بمدينة سرت من وجهة نظر الطالبات (Faculty of Education Scientific Journal, 2024)
Teac hers, performana among secondary school studans sirt (studont,s .views)Thispaper aimed toidentify the tea teachers, per formance among secondary school viens.The samp;ing ofthis study was 100 students who have choser them vandamly. The quantitire method was applied for this study. The instrument was queestionair which con sisted to five terms The results for this study recomondes some recom and ifia Like teachers should upgraded this level consider the positive views and apply modem tequnices to teach them .